2004
DOI: 10.3928/01484834-20040301-08
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Feminist Pedagogy in Empowering a Community of Learners

Abstract: The purpose of this study was to determine whether a pedagogy grounded in feminist ideals has the potential to empower students to make changes consistent with those ideals in their personal and professional lives. In Phase I, qualitative data were collected through e-mail questionnaires from students in two nursing schools, one in Canada and one in the United States. Findings were used to identify an appropriate tool to measure the empowering influence of feminist pedagogy. In Phase 2, a pretest-posttest desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…The three perspectives of empowerment are useful for synthesizing available literature in relation to nursing student empowerment. Researchers in Canada and the United States found that a feminist pedagogy is effective in empowering nursing students (Falk-Rafael et al 2004). From an organization perspective, researchers have used Kanter's (1993) structural empowerment theory as the basis for research: Siu et al (2005) reported that nursing students on a problembased learning programme experienced greater structural empowerment than students on a conventional programme and this increased student motivation, confidence and selfdirection toward learning.…”
Section: Introductionmentioning
confidence: 99%
“…The three perspectives of empowerment are useful for synthesizing available literature in relation to nursing student empowerment. Researchers in Canada and the United States found that a feminist pedagogy is effective in empowering nursing students (Falk-Rafael et al 2004). From an organization perspective, researchers have used Kanter's (1993) structural empowerment theory as the basis for research: Siu et al (2005) reported that nursing students on a problembased learning programme experienced greater structural empowerment than students on a conventional programme and this increased student motivation, confidence and selfdirection toward learning.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Falk‐Rafael () framed core beliefs and expressions of nursing caring within the concepts of social justice, power, and advocacy. In particular, she created the concept of “critical caring” by including both critical feminist theory and nursing feminist theory to public health nursing practice (Falk‐Rafael, Chinn, Anderson, Laschinger, & Rubotzky, ). This “critical caring” includes critique of health inequities, and support for the community as a change agent to correct the imbalance of social power that contributes to health inequities.…”
Section: Introductionmentioning
confidence: 99%
“…In response to these challenges, many teachers are exploring pedagogies new to nursing (e.g. interpretive pedagogies), developing interpretive pedagogies that are discipline-specific, and evaluating the reform emanating from such innovative pedagogical experiences (Ironside 2003a, Falk-Rafael et al 2004). However, while many teachers acknowledge the significance of new pedagogies for reforming nursing education, widespread use of these pedagogies has been slow to enter mainstream nursing education, and the dominance of conventional pedagogy (competency-based or outcomes education) persists (Kawashima 2005).…”
Section: Introductionmentioning
confidence: 99%